Progression and diagnostic challenges of desmoplastic infantile ganglioglioma in a non-infant: a case report with 5-year follow-up - Yang, Yan; Chen, Xuzhu; Liu, Xin; Li, Shiguang (Frontiers in Oncology, 2025)
Desmoplastic infantile ganglioglioma (DIG) is a rare intracranial benign tumor occurring in infants under 2 years of age. It has good biological and behavioral characteristics and occasionally has malignant characteristics, such as multiple intracranial lesions, postoperative progression or recurrence, meningeal diffusion, and metastasis. We present a non-infant with DIG who underwent tumor progression. A 16-year-old girl presented with DIG in the cerebral cistern and underwent subtotal resection. A magnetic resonance imaging (MRI) of the brain 2 years later revealed that the area of abnormal enhancement in the surgical site was approximately the same as before, and follow-up was continued. A reexamination 5 years later showed that the residual extent of the operative area was significantly larger than before and involved the right frontal and temporal lobes, considering the progression of the residual part of the tumor. This case report focuses on the occurrence of DIG and its potential malignant features, as assessed through magnetic resonance imaging.